Protective efficacy and hepatitis B virus clearance in mice enhanced by cell‐mediated immunity with novel prime‐boost regimens. Issue 4 (25th November 2016) - Chuai, X.; Chen, P.; Chen, H.; Wang, W.; Deng, Y.; Ruan, L.; Li, W.; Tan, W.
Summary: In this study, anti‐hepatitis B virus (HBV) immunity was evaluated in mice using several regimens of the HBV recombinant protein vaccine HBSS1 that expressed in CHO cells containing S (1‐223 aa) and preS1 (21‐47 aa) and recombinant adenovirus rAdSS1 vaccine. Further, the protective efficacy of these vaccine regimens was studied in a mouse model. High titres of antigen‐specific antibodies and neutralizing activity were elicited in mice after vaccination. However, robust multi‐antigen (preS1 and S)‐specific cell‐mediated immunity (CMI) was only detected in mice primed with HBSS1 and boosted with rAdSS1. Moreover, functional T‐cell responses with high levels of cytokines and antigen‐specific cytotoxic T‐cell responses (CD107a + CD8 + ) were also detected in the mice. Rapid clearance of hepatitis B surface antigen and HBV DNA in blood and significantly decreased hepatitis B envelope antigen levels were observed in mice immunized with the heterogeneous prime‐boost vaccine after hepatitis B virus challenge by hydrodynamic injection (HI) of pCS‐HBV1.3. The clearance of HBV correlated well with antigen‐specific CMI (Th1 and CTL responses) and cytokine profiles (IFN‐γ, TNF‐α, IL‐2) elicited by vaccination. Taken together, our results might contribute to the development of new human HBV vaccines and a better understanding of the mechanisms underlying immune protection and clearance of hepatitis B virus infection.